Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba PT Citra Pratama Intisetia Makassar - Dasmaniar Dasmaniar; Andi Bau Andriwati; Sangkala Irwan (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
This study aims to analyze the effect of financial ratios on profit growth at PT Citra Pratama Intisetia Makassar during the period 2013–2017. The financial ratios examined include liquidity, solvency, activity, and profitability ratios. This research employs a quantitative approach using secondary data obtained from the company’s financial statements. The data were analyzed using financial ratio analysis and multiple linear regression analysis. The results indicate that the liquidity ratio has a positive and significant effect on profit growth, the solvency ratio has a negative and significant effect on profit growth, the activity ratio has a positive effect on profit growth, while the profitability ratio has a positive but insignificant effect on profit growth. These findings suggest that effective financial ratio management plays an important role in supporting company profit growth.